Efeitos de parâmetros de crescimento nas propriedades ópticas de filmes finos de ZnO:Er - Santos, Camila Ianhez Pereira dos (Universidade Federal de São Carlos, 2019)
We report a systematic study on the structural, morphological and optical properties of Er-doped ZnO thin films grown by Spray Pyrolysis. The films were deposited on glass substrates between 230ºC - 300ºC, using as precursors zinc acetate and erbium chloride in aqueous solution. The effects of growth parameters on erbium optical properties considered the influence of film thickness, the molarity used in the precursor solution and the co-doping with Eu and Mn at different concentrations. The characterization techniques employed to investigate the quality of the films were X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), in which Er, Mn and Eu doped films were analyzed. XRD results indicated that all films are polycrystalline, with wurtzite structure and preferential growth direction on c-axis (002), with no secondary phases. SEM images generally showed that the surfaces have some more porous and cracked regions in the samples synthesized with higher molarity precursor solution, which also had lower crystalline quality. Optical absorbance and photoluminescence spectroscopy (PL) techniques provided data on the influence of different growth parameters on the optical properties of the material. With the first one, Er+3 absorptions related to ground state transitions I(15/2) and levels F(7/2), H(11/2), S(3/2), F(9/2), I(11/2) and I(13/2) were identified. PL showed infrared emissions corresponding to transitions between excited states and the transition from the ground state to the first excited state, at ≈1.53µm. It was possible to identify corresponding emissions between stark levels, generated by the level break due to the effect of the lattice crystalline field. These emissions were less significant for the sample grown with lower molarity precursor solution, indicating that the larger organization of its structure leads to a lower field effect around the Er3+ ions. Co-doping decreased erbium emission intensity, with larger studies of this influence remaining as future perspectives.
Effects of growth parameters on the optical properties of ZnO:Er thin films
Keywords: Érbio; Infravermelho; Fotônica; ZnO; Spray-pirólise; Erbium; Infrared; Photonics; Spray Pyrolysis; CIENCIAS EXATAS E DA TERRA::FISICA